Human GBP1 differentially targets salmonella and toxoplasma to license recognition of microbial ligands and caspase-mediated death - Fisch,D; Clough,B; Domart,M-C; Encheva,V; Bando,H; Snijders,AP; Collinson,LM; Yamamoto,M; Shenoy,AR; Frickel,E-M (Cell Reports, 2020)
Interferon-inducible guanylate-binding proteins (GBPs) promote cell-intrinsic defense through host cell death. GBPs target pathogens and pathogen-containing vacuoles and promote membrane disruption for release of microbial molecules that activate inflammasomes. GBP1 mediates pyroptosis or atypical apoptosis of Salmonella Typhimurium (STm)- or Toxoplasma gondii (Tg)- infected human macrophages, respectively. The pathogen-proximal detection-mechanisms of GBP1 remain poorly understood, as humans lack functional immunity-related GTPases (IRGs) that assist murine Gbps. Here, we establish that GBP1 promotes the lysis of Tg-containing vacuoles and parasite plasma membranes, releasing Tg-DNA. In contrast, we show GBP1 targets cytosolic STm and recruits caspase-4 to the bacterial surface for its activation by lipopolysaccharide (LPS), but does not contribute to bacterial vacuole escape. Caspase-1 cleaves and inactivates GBP1, and a cleavage-deficient GBP1D192E mutant increases caspase-4-driven pyroptosis due to the absence of feedback inhibition. Our studies elucidate microbe-specific roles of GBP1 in infection detection and its triggering of the assembly of divergent caspase signaling platforms.